The Effect of Discipline Development and Work Motivation on the Performance: Empirical Study from Civil Servants at the Spatial Planning Office Bekasi City, Indonesia - Hernandi, Futri Utami; Juddy Prabowo, R.M (Manunggal Halim Jaya, 2024)
The quality of Human Resources (HR) is a critical factor in enhancing the performance of an agency's workforce. Consequently, highly skilled HR is vital for boosting team member performance. At the Bekasi City Spatial Planning Office, it has been noted that employee performance has not yet met the established work standards. Employee performance is influenced by various factors, including the development of discipline and work motivation. This study aims to investigate the extent to which discipline and work motivation contribute to the performance of civil servants at the Bekasi City Spatial Planning Office, both individually and collectively. Utilizing a quantitative research methodology, this study surveyed 45 civil servants from the Bekasi City Spatial Planning Office through random sampling. Data collection was conducted using questionnaires, while data analysis was performed through descriptive and associative methods using SPSS version 26. The findings reveal that the development of discipline positively influences employee performance, whereas work motivation alone does not significantly impact performance. However, when discipline and work motivation are enhanced together, they significantly improve the performance of civil servants at the Bekasi City Spatial Planning Office.